Current Orientations of Surgical–Prosthetic Rehabilitation: Analogue, Digital and Biomechanical Considerations - Gabriele Cervino (Applied Sciences, 2023)
In the last decade, the available digital technologies have made it possible to expand the range of therapeutic options, simplify operational protocols and improve therapeutic plans due to a greater focus on diagnosis and operational protocols [...]